(3GdYfhGf ajeG GNJda ajg GdbQGA GdSHYIs - (3ESeGYjd Hf Nda GdfMhj GdebQj, CHh WGgQ,J (B455 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi PGcQ ai gPG GdcJGH Ef TGA Gddg eG GNJda ajg GdbQGA GdSHYI GdeTghQjf ef CFeI GdCeUGQ HGjLGR hGNJUGQ s
(3BNQgG (B:s
(3hcPdc eG fQcd ShQI MJi jNJe hbO GNJda Yfg ai daX GdJcHjQ hGdPi GNJGQ ef Pdc Gddg CcHQ hced HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3hQOJ CjVkG JMJ Qbe (B"15" (3bQGAGJ hJLhjO (B" (3GdHjGf hGdLeY (B" s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs